Developing a typology for residents and local development: a case study in Northern Greece. (8th July 2020) - Fytopoulou, Eleftheria; Galatsidas, Spyridon; Tampakis, Stilianos; Karasmanaki, Evangelia; Tsantopoulos, Georgios
The understanding of residents' profile and attitude toward local development is critically important since it can guide the efforts to promote local development especially in rural areas which suffer economic disadvantage. Using categorical principal components analysis, categorical regression and cluster analysis, this paper identifies resident types in the Regional Unit of Drama in Greece based on the variables constituting local development and the factors contributing to local development. According to our analysis, the desire for development and development potential were the most important dimensions in local development and these dimensions were affected by participants' demographic characteristics. Moreover, there were three types of residents with the majority belonging to the first type which expressed a positive desire for development and perceived that the region involves a moderate development potential. Moreover, the results can be used to highlight implications for policymakers and local authorities as well as to point to opportunities for future research.